ANALYSIS OF MEMBER SATISFACTION LEVELS ON THE SERVICES OF THE NASARI SAVINGS AND LOANS COOPERATIVE IN THE CITY OF LHOKSEUMAWE - Jariah Abubakar; Furqan, Muhammad; Rizkina, Fathi; Haikal, M.; Sinta, Irada (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The Nasari Savings is needed to find out the perceptions of a member about the services and performance of the management that has been carried out. To assess and examine the satisfaction of members, several dimensions can be used as measurement tools. The study was aimed to determine the level of satisfaction of members of the Cooperative. This study used a qualitative descriptive method with a total sample of 96 people. The sampling technique uses simple random sampling technique and data is collected through a questionnaire. The indicators of service; office strategic elements, cleanliness and comfort of office space, the availability of complete office facilities such as computers, printers and office telephones, transaction execution systems, accuracy in services, information clarity given by employees, the readiness of employees to receive complaints from members, the willingness and ability of employees to provide the information needed, the readiness of employees in providing services, knowledge, skills and skills of employees in their fields, beliefs about security, cooperative legal certainty, attention given by employees against member complaints, employees provide services to all members regardless of social status, employees always maintain good communication with members are included to Very Good performances.